Exclusive breastfeeding: knowledge, attitude, practice, and its determinants among Malay mothers in Ampang, Selangor - Johari, Basma; Mohd Shukri, Nor Azwani (IIUM Press, International Islamic University Malaysia, 2018)
Exclusive breastfeeding (EBF) for up to six months is internationally recommended due to its benefits for both maternal and infant health. However, the rate of EBF in Malaysia is still below the desirable levels. This study examined the prevalence of EBF and assessed the knowledge, attitude, and practice (KAP), and determinants of breastfeeding among Malay mothers in Ampang, Selangor. Ninety-two Malay subjects who breastfed healthy children aged six to 36 months, were included in this study. Data were collected by dual-language, self-administered questionnaire (which included Iowa Infant Feeding Attitude Scale, IIFAS), to determine KAP of mothers towards breastfeeding. Socio-demographic, psychosocial, and environmental factors related with EBF were also assessed. Linear logistic regression model was used to identify factors that may determine breastfeeding for six months (exclusively) and beyond. A total of 28% of the subjects practised EBF up to six months, 39% less than six months, and 33% continued BF beyond six months. The mean IIFAS total score was 66.1 ± 8.11, which ranged between Neutral and Positive towards Breastfeeding Practice attitudes. Higher IIFAS score is related to intended and actual exclusive breastfeeding. Several variables were significantly related to breastfeeding for six months (exclusively) and beyond. This included maternal age of 30 years or more (OR:3.26, 95% CI:1.27–8.38); higher socioeconomic status (OR:8.50, 95% CI:1.76– 41.06); higher educational level (OR:5.21, 95% CI:1.66–16.34); multi-parity (OR:3.15, 95% CI:1.17–8.47); nonworking status (OR:3.81, 95% CI:1.02–14.3); support from spouse (OR:2.39, 95% CI:1.01–5.65); availability of private rooms for breastfeeding at workplace (OR:4.30, 95% CI:1.77–10.63); and child birth place (OR:2.54, 95% CI:1.08– 5.98). The right maternal knowledge and attitude play crucial roles in the success of breastfeeding. Hence, more health promotion is needed. Supports from spouse, workplace, and hospital staff after delivery, are also essential to improve EBF statistics in Malaysia.